Breastfeeding is associated with reduction in postpartum depression in the United Arab Emirates: a retrospective cross-sectional study - Ala Al Rajabi (22457746) (2025)
Postpartum Depression (PPD) is a common mental health disorder affecting mothers. Breastfeeding may be protective against PPD. Global estimates of breastfeeding and PPD rates vary, especially for women living in Middle Eastern countries. The current study aims to assess breastfeeding and PPD prevalence and to identify factors associated with reduced PPD risk within the social and cultural contexts of the UAE. We used a purposive, convenience snowball sampling technique to recruit participants. Inclusion criteria were female ≥ 18 years, mother of a child ≤ three years, and resident of Abu Dhabi, UAE. Data was collected using an online survey distributed via email and social media platforms. The survey comprised four sections: sociodemographic characteristics, breastfeeding behaviour, Edinburgh Postnatal Depression Scale (EPDS), and The International Physical Activity Questionnaire –Short Form (IPAQ-SF). Pearson chi-squared tests and binary logistic regression model were used to investigate the associations between PPD levels and potential predictors using SPSS statistical software. Variables included in the regression model were breastfeeding duration, delivery mode, BMI, education, general health, physical activity level, employment status, number of children, and age. All statistical significance was considered at p-value < 0.05. In total 403 subjects consented to participate; 204 met the inclusion criteria and were included in the final analysis (age [mean ± SD] = 31.2 ± 7.3 years). Among them, 34.8% suffered from moderate-to-severe PPD, and 66.2% breastfed their last child for > 3 months. Regression model results showed that (OR; 95% CI) college education (0.39; 0.19–0.80), having more than one child (0.40; 0.17–0.94), self-reported very good (0.43; 0.19–0.98) and excellent health (0.21; 0.08–0.51), and breastfeeding for > three months (0.46; 0.23–0.92), were significantly associated with reduced odds of moderate-to-severe PPD. None of the remaining variables -including physical activity- were significant. In conclusion, breastfeeding is significantly associated with a reduction in moderate-to-severe PPD among mothers in Abu Dhabi, UAE. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-025-94912-3